Maternal prenatal paracetamol ingestion and scholastic attainments of the offspring - Jean Golding; Holly Tunstall; Steven Gregory; Yasmin lies-Gaven (Frontiers Media S.A., 2023)
Background: Fetal exposure to paracetamol (acetaminophen) has been shown to be associated with asthma and other atopic disorders, as well as behavioural problems including hyperactivity, in childhood. However, there is little information on scholastic abilities among children exposed to paracetamol in pregnancy.Objectives: To determine whether there are any differences in scholastic abilities among the offspring of women who ingested paracetamol during pregnancy compared with non-exposed children.Methods: Mothers enrolled in the Avon Longitudinal Study of Parents and Children (ALSPAC) had recorded the frequency with which they had taken the medication over two time periods during pregnancy: i) the first 18 weeks and ii) 18-32 weeks. The offspring have been followed up ever since. For this study we use as outcomes: a) 14 tests of ability at reading and 2 of spelling using the study's tests and the national education system test results; b) 6 of mathematical abilities including tests of arithmetic and mathematical reasoning, and c) 1 of scientific understanding. Multiple regression was used, adjusting for 15 different exposures including reasons for taking the medication as well as demographic features.Results: Almost all unadjusted and adjusted mean differences were negative (i.e., those exposed to maternal intake of paracetamol did less well), but negative associations for exposures between 18 and 32 weeks of gestation were much more evident than for exposures earlier in pregnancy. Of the later exposures, after adjustment, 12 of the 23 scholastic tests were associated with prenatal exposure to paracetamol at p < 0.05. These negative effects were found in the girls (12 tests at p < 0.05) but not boys (0 tests at p < 0.05).Conclusion: Evidence from this longitudinal study suggests that maternal exposure to paracetamol is associated with disadvantages to the offspring in scholastic abilities such as mathematics and reading at secondary school ages. This raises the question as to whether there are longer-lasting effects on educational attainment from age 15 years onwards, including at university level. Clearly these results should be tested in other settings, but meanwhile they add to a growing accumulation of known adverse effects of exposure to paracetamol in pregnancy.